ACCOUNTING FOR ISLAMIC SOCIAL FINANCE AND INCLUSIVE GROWTH IN INDONESIA - Muhammad Putra Aprullah; Raida Fuadi; Rita Meutia; Indrayani Indrayani; Muhammad Sayuthi; Agus Adria; Salsabilla Julnadi; Zahara Zahara (Worksheet : Jurnal Akuntansi, 2026)
Indonesia faces multidimensional challenges in escaping the middle-income trap and attaining high-income status by 2045. Although economic growth has been relatively stable (averaging 4.9% from 2000 to 2022), poverty reduction has plateaued at around 10%, indicating that growth has not been sufficiently inclusive. In parallel, Indonesia—home to the world’s largest Muslim population and ranked first in the 2021 World Giving Index—has substantial potential to scale Islamic Social Finance (ISF).Using a Systematic Literature Review (SLR), this article critically examines the strategic role of key ISF instruments—zakat, infaq/sadaqah, and waqf—in poverty alleviation, inequality reduction, and inclusive development in Indonesia, with particular emphasis on the accounting dimensions of recognition, measurement, reporting, and accountability. The review indicates that the estimated national zakat potential of IDR 327 trillion could finance up to 76% of the government’s social protection budget. In addition, cash waqf provides a sustainable social investment model that can support long-term funding for education, health, and MSME empowerment. However, ISF optimization remains constrained by low literacy, fragmented governance, limited transparency, and weak policy integration—issues that are closely linked to the quality of financial reporting, disclosure practices, internal control systems, audit/assurance, and governance mechanisms within ISF institutions. This study concludes that ISF should be positioned not merely as philanthropy, but as an accountable, measurable socio-economic instrument that complements public fiscal policy, strengthens the social protection architecture, and supports the achievement of an equitable “Golden Indonesia 2045.”